Use of paired serum sample for the diagnosis of toxoplasma infection in selected population by using elecsys toxo IgG/IgM in HUSM - Thangarajah, Padmaloseni (2018)
Introduction Toxoplasmosis is one of the most common worldwide parasitic infection due to Toxoplasma gondii, an obligate intracellular parasite. The mode of transmission is through consumption of food or water or undercooked meat contaminated with the parasite. Maternal infection with vertical transmission depends on age of gestation. Severity of infection is during early gestation, may lead to intense complications such as intrauterine death (IUD) or later with increased risk of congenital infection. In ocular toxoplasmosis, reactivation of infection are common among immunocompromised and immunocompetent patients. Serology is still the mainstay for the diagnosis of Toxoplasma infection. Therefore, this method was applied with paired serum sample in selected population using Elecsys Toxo IgG/IgM assay in HUSM. The paired serum sample was to classify the infection into early, acute, reactivation, recent, latent, possible congenital infection and passive immunity from mother. This study aimed to describe the clinical manifestation, determine the seroprevalence classification of infection among the selected populations, validity of the test and percentage of patient on treatment after first and paired serum sample.